New technique for radiolabelling tracer with 64CU for positron emission particles tracking (PEPT) experiments - Liu, Cong (Department of Chemical Engineering, 2015)
Positron emission particle tracking (PEPT) is a non-invasive technique for studying the flow of particulate systems within industrial equipment. The technique tracks a tracer particle labelled with a positron emitting radionuclide moving within the field-of-view of a positron emission tomography (PET) scanner. Two important components of the technique are a PET camera and PEPT tracers, which are particle tracers labelled with a positron emitting radionuclide. Currently, the majority of PEPT tracers are made with 68Ga or 18F. However, the relatively short half-life of these two radionuclides limits the application of PEPT to a maximum of 3 hours of experimental time. 64Cu is a potential candidate for PEPT tracer fabrication due to its relatively long half-life (12.7 h) which could extend the experimental running time of PEPT experiments to two uninterrupted days. The objective of the research described in this thesis was to develop a technique for radiolabelling tracers with 64Cu, and to test their efficacy in PEPT experiment. The work was conducted at Radionuclide Production Department, iThemba LABS near Cape Town, where high purity 64Cu was obtained by a two stages separation method using ion exchange chromatography.